The First International Seminar Poltekkes Kemenkes Palangka Raya: A Journey Full of Meaning - Yeyentimalla, Yeyentimalla; Sera, Agnescia Clarissa; Sinaga, Doni Marisi (GHMJ (Global Health Management Journal), 2022)
Poltekkes Kemenkes Palangka Raya in collaboration with Indonesian Scholars' Alliance and Global Health Management Journal (GHMJ) successfully held the first international seminar on November 9, 2020. The seminar which took place online in the midst of the raging Coronavirus Disease 2019 (COVID-19) pandemic raised the theme "The New Normal: Creating A Pleasant Virtual Communication”. Five speaker from four countries namely Prof Andrew J. Macnab (Canada), Sr. Merceditas O. Ang, SPC (Philippines), Eva Berthy Tallutondok, M.Sc. (Taiwan), Dr. Yeyentimalla (Poltekkes Kemenkes Palangka Raya, Indonesia), and Prof. Sri Suryawati (Universitas Gadjah Mada, Indonesia) synergizes to convey ideas on how to create fun virtual communication actors. During the pandemic, we do not communicate face-to face, but instead switch to communication using technological devices and chating application. Adequate understanding is needed to be able to communicate with other people virtually where messages are conveyed well and at the same time happy. The journey to the seminar in about four months presents a variety of emotions with negative and positive valences. For example, how to create a seminar participant and photo essays registration website with an inexperienced committee and communication is done virtually. In many ways we argued loudly. This level of difficulty is quite high. Virtual communication is different from face-to-face. We have to be more selective with words because intonation and gesture are absent in communication via WhatsApp and Facebook Messenger. We optimize virtual communication right before we teach it to seminar attendees! This is so much fun! Pandemic may isolate our body, not our ideas. The international seminar was held on Monday, November 9, 2020, to coincide with the 19th anniversary of the founding of the Poltekkes Kemenkes Palangka Raya. In accordance with the health protocol during the COVID-19 pandemic, the online committee from home and from their respective workspaces does not gather in one room. Seminar participants attended the Zoom room after previously registering through the website. At the end of the registration period, 32 photo essays obtained. The details are 16 photo essays from the Department of Nursing, 9 photo essays from the Department of Midwifery, and 7 photo essays from the Department of Nutrition. On November 9, 2020, after the seminar was over, 9 photo essays winners from 9 categories were announced, and been published at the Global Health Management Journal as 2022's Special Edition, following the standard guidelines for Photo Essays.